FAKTOR-FAKTOR YANG MEMENGARUHI ANGKA KEJADIAN KANKER SERVIK DI RSUD MARGONO SOEKARJO PURWOKERTO - Susilo Rini; Fauziah Hanum N.A (Universitas Harapan Bangsa Purwokerto, 2016)
Cervical cancer is the growth of a group of abnormal cells in the cervix (mouth of the womb).According to WHO (2015), an estimated 9 million people who died of cancer. Cervical cancer fromdeveloping countries amounted to 1.064 million cases, incidence rates in developing countries arestill relatively high (MOH 2010). Central Java province in 2012 as many as 2,259 cases (19.92%)of the total number of 11 341 cancer cases. The number of cases of reproductive disorders inpatienthospital treatment Prof. Dr. Margono Soekarjo Purwokerto in the year 2015 as many as 28 695cases with 757 cases of cervical cancer. Risk factors for cervical cancer include HPV infection, thenumber of sexual partners, sexual activity the first time, age, frequency of pregnancy, smoking, useof the pill kontrasepai, immune, race. The purpose of this study is to look at the factors associatedwith the incidence of cervical cancer. This research was conducted using the method of correlationanalysis. Bivariate analysis using person correlation analysis. The population is all cervical cancerpatients in RS Margono Soekarjo 2015. The sample is taken by quota sampling of 100 patients. Statistical test results, the age factor obtained P value of 0.001, the parity factor values obtainedSig. (2-tiled) of 0.539, and contraceptive history factor values obtained Sig. (2-tiled) amounted to0,064. Keywords: Factors, Cervical Cancer